2005
DOI: 10.1037/0021-9010.90.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Leader Self-Sacrifice and Leadership Effectiveness: The Moderating Role of Leader Prototypicality.

Abstract: Daan van Knippenberg Erasmus University RotterdamSelf-sacrificing behavior of the leader and the extent to which the leader is representative of the group (i.e., group prototypical) are proposed to interact to influence leadership effectiveness. The authors expected self-sacrificing leaders to be considered more effective and to be able to push subordinates to a higher performance level than non-self-sacrificing leaders, and these effects were expected to be more pronounced for less prototypical leaders than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
464
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(499 citation statements)
references
References 70 publications
26
464
3
6
Order By: Relevance
“…5 Without prototypicality included as an independent variable in the analyses, the Procedural Fairness Self ϫ Procedural Fairness Others interaction was significantly related to cooperation in Studies 1 and 3 but not in Studies 2 and 4 of the present research project. Research shows that prototypical group leaders are more effective (B. van Knippenberg & van Knippenberg, 2005) and are also perceived as such (e.g., Hains et al, 1997), and the present research shows that prototypical leaders are also more effective in using fair procedures to increase cooperation toward the group's goals. However, the reality of organizational life is that supervisors often do not emerge on the basis of their prototypicality but are appointed by higher management.…”
Section: Practical Implicationsmentioning
confidence: 65%
See 2 more Smart Citations
“…5 Without prototypicality included as an independent variable in the analyses, the Procedural Fairness Self ϫ Procedural Fairness Others interaction was significantly related to cooperation in Studies 1 and 3 but not in Studies 2 and 4 of the present research project. Research shows that prototypical group leaders are more effective (B. van Knippenberg & van Knippenberg, 2005) and are also perceived as such (e.g., Hains et al, 1997), and the present research shows that prototypical leaders are also more effective in using fair procedures to increase cooperation toward the group's goals. However, the reality of organizational life is that supervisors often do not emerge on the basis of their prototypicality but are appointed by higher management.…”
Section: Practical Implicationsmentioning
confidence: 65%
“…Then, we introduced the prototypicality manipulation (taken from B. van Knippenberg & van Knippenberg, 2005). Participants individually completed a brain-hemisphere dominance test and received bogus feedback concerning their own and other group members' scores on this test.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, leaders who are able to create 5 shared social identification between themselves and group members are more likely to be supported (van Dijke and De Cremer 2010), perceived as trustworthy (Geissner and van Knippenberg 2008), influential (Subasic et al 2011), andeffective (van Knippenberg andvan Knippenberg 2005). Thus, the unified group is more likely to work together towards collective targets.…”
Section: Leading For Gold: Social Identity Leadership Processes At Thmentioning
confidence: 99%
“…An example of this could include the leader allocating time to communicate with each member of staff on an individual or sub-group basis during the dynamic phases of change. Researchers have demonstrated that such leaders who represent their group's identity content are perceived as more effective (van Knippenberg & van Knippenberg, 2005), trustworthy (Geissner & van Knippenberg, 2008), and charismatic (van Dijke & De Cremer, 2010). Furthermore, to continue to facilitate change, leaders may consider explicitly communicating and reinforcing the collective meanings developed by the group during the reflecting stage.…”
Section: Representationmentioning
confidence: 99%